Terbinafine and risperidone drug interaction contributing to clinical changes in a forensic psychiatric patient - Reynolds Jamie PharmD; Gramlich Nicole PharmD, BCPP (American Association of Psychiatric Pharmacists, 2023)
Risperidone is a second generation "atypical" antipsychotic that exhibits its clinical effects through a combined effort of risperidone and its active metabolite, 9-hydroxyrisperidone (9-OHR), otherwise known as paliperidone. Risperidone is hepatically metabolized by the cytochrome P450 2D6 (CYP2D6) enzyme into 9-OHR. Significant interference with the metabolism of risperidone may lead to clinical consequences for patients via alterations in the ratio of the parent compound and active metabolite. This patient case reports 1 example of how a drug interaction could contribute to delayed response to a medication increase after psychiatric decompensation. A forensic psychiatric patient was transitioned from oral risperidone to risperidone microspheres long-acting injectable and had worsening of symptoms, necessitating an increased dose of the injection. This increase in symptoms may have been prolonged by addition of a CYP2D6 inhibitor, terbinafine. The changes in clinical symptoms correlate with medication concentrations that were drawn before terbinafine was started, during terbinafine therapy, and after terbinafine was discontinued.